2019
DOI: 10.1016/j.ttbdis.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A countrywide molecular survey leads to a seminal identification of the invasive cattle tick Rhipicephalus (Boophilus) microplus in Cameroon, a decade after it was reported in Cote d’Ivoire

Abstract: The cattle tick Rhipicephalus microplus is the most important arthropod vector of livestock diseases globally. Since its introduction in West Africa a decade ago, it has been reported in Ivory Coast, Benin, Togo, Mali, Burkina Faso and Nigeria with potentially far-reaching adverse impacts on the livestock sector in the region. Cameroon is located on a major route for transboundary cattle trade between Central and West Africa and it is therefore at risk from R. microplus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 53 publications
6
37
0
Order By: Relevance
“…Low et al, (2015) [20] reported a relatively low but signi cant genetic differentiation of R. microplus in Malaysia while in S. African a low variation within the species was observed with COI and 16S rDNA genes [38]. A similar low divergence was also recently observed in Cameroonian R. microplus ticks by Silatsa et al, (2019) [10] using the two mitochondrial genes. Low levels of genetic differentiation and lack of population structuring amongst R. microplus populations based on microsatellite markers has also been observed [38][39][40].…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Low et al, (2015) [20] reported a relatively low but signi cant genetic differentiation of R. microplus in Malaysia while in S. African a low variation within the species was observed with COI and 16S rDNA genes [38]. A similar low divergence was also recently observed in Cameroonian R. microplus ticks by Silatsa et al, (2019) [10] using the two mitochondrial genes. Low levels of genetic differentiation and lack of population structuring amongst R. microplus populations based on microsatellite markers has also been observed [38][39][40].…”
Section: Discussionsupporting
confidence: 58%
“…6). The same low divergence has also been observed with the 16S rDNA gene [10,20]. R. microplus, a one-host tick that completes its entire life cycle attached to a single vertebrate host can be classi ed as a host specialist [41].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations